REDUCTION OF FORMALDEHYDE EMISSION FROM WOOD-BASED PANELS BY MODIFICATION OF UF ADHESIVES WITH NATURAL BIOPOLYMERS - Matyašovský, Ján; Sedliačik, Ján; Duchovič, Peter; Novák, Igor (Innovation in Woodworking Industry and Engineering design, 2023)
At present, polycondensation urea-formaldehyde (UF) resins are the most widely used wood gluing adhesives, but their main disadvantage is their low resistance to water and moisture, which causes the subsequent release of formaldehyde emissions from finished products. The aim of the study was to reduce the release of formaldehyde from wood materials by developing and testing new, more effective modifiers that bind formaldehyde or form more stable methylene bonds during polycondensation. Research was focused on the biopolymer collagen and keratin. For this study collagen samples were modified with hardener RODA M 210 (manufacturer Duslo Šaľa) and sulphur additive. From biopolymer keratin, which can be found in hair, feather, wool, nails, hoofs, horns, etc., were prepared samples by thermal heating during for 1 hour at various temperatures from 150°C to 197°C. XPS Ray photoelectron spectroscopy analyse was used to identify changes in their surface chemical structure. The XPS spectrum of keratin samples has been shown to depend on the temperature of their thermal degradation, with the total amount of carbon, nitrogen and sulphur increasing with increasing temperature. For sulphur, the total amount of its reduced form expressed as sulphide also increases, while the total amount of oxygen decreases with increasing temperature. Technical applications have focused on the application of keratin samples to modify mixtures of UF resins to reduce the release of formaldehyde from glued wood-based panels. Formaldehyde emissions were assessed from five-layer plywood according to EN ISO 12460-4. Measured values of extinctions of tested samples confirmed the decrease of formaldehyde emissions for each concentration of collagen and keratin samples in comparison with the reference sample.